Clinical features and response to immune combinations in patients with renal cell carcinoma and sarcomatoid de-differentiation (ARON-1 study) - Ciccarese, Chiara; Büttner, Thomas; Cerbone, Linda; Zampiva, Ilaria; Monteiro, Fernando Sabino M; Basso, Umberto; Pichler, Martin; Vitale, Maria Giuseppa; Fiala, Ondrej; Roviello, Giandomenico; Kopp, Ray Manneh; Carrozza, Francesco; et al. (International journal of cancer, 2024)
Metastatic renal cell carcinoma (mRCC) carrying sarcomatoid features (sRCC) has aggressive biology and poor prognosis. First-line immunotherapy (IO)-based combinations have improved the outcome of clear cell RCC patients, including that of sRCC. Real-world data confirming the adequate first-line management of sRCC is largely lacking. We investigated the clinical features and the outcome of sRCC patients treated with IO-based combinations within the ARON-1 study population (NCT05287464). The primary objective was to define the incidence and baseline clinical characteristics of sRCC compared with non-sRCC patients. The secondary objective was to describe the outcome of sRCC patients based on type of first-line treatment (IO + IO vs. IO + tyrosin kinase inhibitor [TKI]). We identified 1362 mRCC patients with IMDC intermediate or poor risk, 226 sRCC and 1136 non-sRCC. These two subgroups did not differ in terms of baseline characteristics. The median overall survival (OS) was 26.8 months (95%CI 21.6-44.2) in sRCC and 35.3 months (95%CI 30.2-40.4) in non-sRCC patients (p = .013). The median progression-free survival (PFS) was longer in non-sRCC patients compared to sRCC (14.5 vs. 12.3 months, p = .064). In patients treated with first-line IO + TKI the median OS was 34.4 months compared to 26.4 months of those who received IO + IO (p = .729). The median PFS was 12.4 months with IO + TKI and 12.3 months with IO + IO (p = .606). In conclusion, we confirm that sRCC are aggressive tumors with poor prognosis. IO-based combinations improve survival outcomes of sRCC patients, regardless from the type of strategy (IO + IO versus IO + TKI) adopted.
Keywords: senioři; Carcinoma, Renal Cell; senioři nad 80 let; Protein Kinase Inhibitors; Prognosis; lidé; Middle Aged; mužské pohlaví; karcinom z renálních buněk; Adult; Kidney Neoplasms; Aged, 80 and over; ženské pohlaví; prognóza; imunoterapie; Humans; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; Immunotherapy; inhibitory proteinkinas; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; nádory ledvin; Male